Renal Protective Effect of Sulbutiamine, Thiamine, Riboflavin and their Combinations on Vancomycin-Induced Acute Renal Failure in Male Rats - Dayan K. Jabbar; Jasim, Ghaith A.; Al-Ezzi, Muthana I. (Iraqi Journal of Pharmaceutical Sciences, 2025)
Background: The main mechanisms thought to be involved in the pathophysiology of acute renal failure with vancomycin treatment are oxidative stress, inflammation and apoptosis. In this study we evaluated the potential effects of sulbutiamine, thiamine, riboflavin and their combinations on vancomycin-induced acute renal failure as well as the underlying mechanisms. Methods: a model of vancomycin-induced acute renal failure was performed on male rats. Forty-two rats were separated randomly into seven groups: group 1 (a control group), group 2 (induction vancomycin group) given 200mg/kg at 3rd week, group 3 (sulbutiamine + vancomycin), group 4 (thiamine + vancomycin), group 5 (riboflavin + vancomycin) group, group 6 (sulbutiamine+ riboflavin + vancomycin) and group 7 (thiamine+ riboflavin + vancomycin). Results: in rats’ model with vancomycin-induced acute renal failure, sulbutiamine, thiamine, riboflavin and their combinations could protect against vancomycin-induced acute kidney injury which included histological damage, renal dysfunction, and elevated craetinine and blood urea nitrogen levels. Furthermore, increased immune-expression of kidney injury molecule-1 and tumor necrosis factor-alpha resulted from vancomycin treatment also ameliorated by sulbutiamine, thiamine, riboflavin and their combinations. Conclusions: The findings showed that sulbutiamine, thiamine, riboflavin and their combinations protected against nephrotoxicity caused by vancomycin by relieving renal functions and reducing the level of expression of Kim-1, TNF-alpha and attenuating histopathological alterations through their anti-oxidative and anti-inflammatory characteristics. The sulbutiamine and its combination with riboflavin giving the best results in attenuating vancomycin-induced acute renal failure. The research also revealed an additional effect of sulbutiamine with riboflavin.